TikTok as Learning Media: Challenges and Opportunities in Vocational Education: A Descriptive Qualitative Study at SMK Yuppentek 2 Tangerang - Alamsyah Riky Wardana; Feri Johansah; Arrum Dara Efda (Journal of Education and Teaching Learning, 2026)
Short-video platforms have become an important part of young people's media consumption, raising interest in their potential as learning tools. This study explores the challenges and opportunities of using TikTok as a learning medium at SMK Yuppentek 2, a vocational high school in Tangerang, Indonesia, using a descriptive qualitative approach. Data were collected through in-depth interviews with ten informants, supported by observation and documentation, and analyzed using the Miles and Huberman interactive model with source and method triangulation. The findings show that students mainly perceive TikTok as an entertainment platform. The main challenges include algorithm-driven distractions, limited depth of short-form content, unequal internet access, and the lack of systematic classroom integration. Despite these limitations, TikTok supports vocational skill demonstrations, self-directed learning, creativity, digital literacy, and school promotion. Viewed through the distinction between gratifications sought and gratifications obtained, the findings indicate that TikTok's educational value depends on its ability to meet students' learning motivations and expectations. Therefore, TikTok has the potential to serve as a complementary learning medium in vocational education when supported by appropriate instructional strategies.